Malignant melanoma associated with congenital melanocytic nevus and diagnosed with intestinal metastases: Two case reports - Nilüfer ONAK KANDEMİR; Burak BAHADIR; Sibel BEKTAŞ; Figen BARUT; Gamze YURDAKAN; Banu DOĞAN GÜN; Hüseyin ENGİN; Selim AYDEMİR; Şükrü Oğuz ÖZDAMAR (Turkish Journal of Gastroenterology, 2019)
-